Spatial and temporal analysis of the highly pathogenic avian influenza H5N1 outbreak in the Dombes area, France, in 2006 - Doctrinal, Delphine; Ruette, Sandrine; Hars, Jean; Artois, Marc; Bicout, Dominique J (Wildfowl, 2013)
In February 2006, the highly pathogenic H5N1 strain of the avian influenza virus was confirmed as being the cause of death for three Common Pochard Aythya ferina recovered at the same time from a pond in the Dombes, France. The subsequent epizootic lasted for 65 days in the Dombes region, with the last occurrence of the H5N1 strain of the virus confirmed on 18 April. Data recorded for dead wild birds collected on ponds and confirmed as being positive for the H5N1 strain of avian influenza were used to develop a pond-level analysis of the H5N1 outbreak. The outbreak was found to be limited mainly to Common Pochard and Mute Swan Cygnus olor, which were found dead at 20 of about 1,200 ponds in the Dombes. The outbreak was confined to an area of about 15 km in diameter, with two spatio-temporal clusters of ponds where birds had contracted the disease. The findings are used to assess the potential role played by wild waterfowl in avian influenza epidemiology and to suggest possible scenarios for the introduction and spread of the virus at a local scale based on analysis of its occurrence in the Dombes.